Examining the key performance indicators of all-star players and winning teams in elite futsal - Santos, J.; Mendez-Dominguez, C.; Nunes, C.; Gómez, M. A.; Travassos, B. (International Journal of Performance Analysis in Sport, 2020)
Purpose: to identify the key performance indicators that discriminate all-star from non-all-star players; and to differentiate winning from drawing/losing teams during the Euro Cup 2018 Futsal (Slovenia). Methods: the sample consisted of all matches (n = 20) played by 12 teams (87 players). Differences between both players and teams were calculated using the Mann-Whitney U and student-t tests and the binary logistic regression (assessing the relationship between all-star players or winning teams and several match- and contextually based variables). Results: minutes per match, goals, assists, ball recoveries, % shots on target, % key pass accuracy, and % challenges won discriminated all-star from non-all-star players. However, only minutes per match (OR: 1.329), goals (OR: 13.547), and ball recoveries (OR: 2.136) per time played were determined to differentiate all-star players. Regarding the team analysis, the following variables discriminated winning from losing/drawing teams: goals, assists, % counterattack success, and % set pieces success. However, only goals (OR: 2.035) and % set piece success (OR: 1.076) predicted the match outcome. Conclusions: the current findings can help coaches to a better understanding of which key performance indicators are important out of all data available, contributing to defining priorities when training and managing competition in elite futsal.